An improved particles model for stress sensitivity in low-permeability sandstones. Issue 2 (3rd March 2016) - Gai, S. H.; Liu, H. Q.; He, S. L.; Lei, G.; Mo, S. Y.; Huang, X.; Yang, Y.; Chen, X.
Abstract: Stress-dependent permeability and porosity of porous media is very important for the development of oil reservoirs, especially in low-permeability reservoirs. Porous structure can change in response to an increase in the effective stress to induce the decline of permeability and porosity, which ultimately affects the fluid flow property. In this study, a capillary module, considering the arrangement and the deformation of particles, has been established to express the stress sensitivity of porous media based on the particle packing model. The predictions of variation of permeability by the proposed model have been validated by comparing with the experimental data. The predictions by the current model show the same variation trend with the experimental data and are consistent with the compression experiments. The proposed variation of permeability with the increase in effective stress depends on the factors such as the arrangement of particles (contact angle), the deformation of particles (elastic module and Poisson's ratio) and effective stress. The effects of these parameters on variation of permeability are discussed in detail.